The impact of political communication on the value formation in Ukrainian society during the crisis - Шмаленко, Юлія Іванівна; Шмаленко, Ю. І.; Shmalenko, Yuliia I.; Матвієнків, Світлана Миколаївна; Матвієнків, С. М.; Matviienkiv, Svitlana M.; Луцишин, Галина Іванівна; Луцишин, Г. І.; Lutsyshyn, Halyna I.; Анісімович-Шевчук, Ольга Зенонівна; Анісімович-Шевчук, О. З.; Anisimovych-Shevchuk, Olha Z.; et al. (Vilnius : UKAPA, 2025)
The study examines the impact of political communication on the formation and transformation of values in Ukrainian society during the crisis caused by Russian military aggression. The aim of the study is to analyze the impact of political communication on the formation of public values in Ukraine during the current crisis. The analysis of sociological data revealed significant changes in public attitudes and value orientations of Ukrainians after the start of a full-scale Russian invasion in 2022. The study employs a mixed-method approach, combining methods of quantitative sociological public opinion polling, content analysis, statistical analysis, and qualitative evaluation of political messaging strategies. The obtained data indicate a significantly increased support for European integration, increased trust in political institutions, intensified feeling of national unity and cohesion of European integration, and democratic ideals. The effectiveness of the government’s multi-channel communication strategy, combining traditional mass media and social networks, was revealed. The study demonstrates regional differences in changes in value orientations, with the greatest increase in pro-European attitudes in the South and East of Ukraine. National stability, European integration, sovereignty, and territorial integrity are defined as key topics of political communication. The study also emphasizes that effective political communication in Ukraine during the crisis contributed to significant transformations of social values. Furthermore, communication proved to be an important tool for mobilizing public support, social cohesion, and strengthening national identity. Recommendations are provided for effective public engagement and promotion of values that strengthen national unity and democratic institutions during a crisis. Further research may focus on the development of strategic ways of supporting positive changes in the post-conflict period.
Shmalenko I. The impact of political communication on the value formation in Ukrainian society during the crisis / I. Shmalenko, S. Matviienkiv, H. Lutsyshyn et al. // Public Policy and Administration. – Vilnius : UKAPA, 2025. – 24(2). - P. 385 – 400. URL: https://doi.org/10.13165/VPA-25-24-2-16
Keywords: political communication; society; values; crisis; public opinion; national unity